Frequency and clinicopathologic associations of DNA mismatch repair protein deficiency in ampullary carcinoma: Routine testing is indicated. Issue 21 (28th August 2020) - Xue, Yue; Balci, Serdar; Aydin Mericoz, Cisel; Taskin, Orhun C.; Jiang, Hongmei; Pehlivanoglu, Burcin; Muraki, Takashi; Memis, Bahar; Saka, Burcu; Kim, Grace E.; Bandopadhyay, Sudeshna; Knight, Jessica; et al.
Abstract : Background: The significance of DNA mismatch repair (MMR) deficiency in ampullary cancers (ACs) has not been established. Methods: In total, 127 ACs with invasive carcinomas measuring ≥3 mmthat had adequate tissue were analyzed immunohistochemically. Results: MMR loss was detected in 18% of ACs (higher than in colorectal cancers). Twelve tumors with MLH1‐PMS2 loss were negative for BRAF V600E mutation, suggesting a Lynch syndrome association. MMR‐deficient tumors (n = 23), comparedwith MMR‐intact tumors (n = 104), showed a striking male predominance (male:female ratio, 4.7). Although the deficient tumors had slightly larger invasion size (2.7 vs 2.1 cm), they also had more expansile growth and less invasiveness, including less perineural invasion, and they ultimately had lower tumor (T) classification and less lymph node metastasis (30% vs 53%; P  = .04). More important, patients who had MMR‐deficient tumors had better clinical outcomes, with a 5‐year overall survival rate of 68% versus 45% ( P  = .03), which was even more pronounced in those who had higher Tclassification (5‐year overall survival, 69% vs 34%; P  = .04). MMR deficiencyhad a statistically significant association with medullary phenotype, pushing‐border invasion, and tumor‐infiltrating immune cells, and it occurred more frequently in ampullary‐duodenal type tumors. Programed cell death‐ligand 1 (PD‐L1) levels analyzed in the 22 MMR‐deficient ACs revealed that all medullary carcinomas were positive. Nonmedullary MMR‐deficient carcinomas expressed PD‐L1 in 33% of tumors cells according to the criteria for a combined positive score ≥1, but all were negative according to the tumor proportion score≥1 method. Conclusions: In ACs, MMR deficiency is even more frequent (18%) than in colon cancer and often has a Lynch‐suggestive profile, thus routine testing is warranted. Male gender, pushing‐border infiltration, ampullary‐duodenal origin, medullary histology, and tumor‐related inflammation have a significantly higher association with MMR deficiency. MMR‐deficient tumors have less aggressive behavior. PD‐L1 expression is common in medullary‐phenotype ACs, thus immunotherapy should be considered at least for this group. Abstract : In ampullary carcinomas, mismatch‐repair deficiency is seen as often as, if not more frequently than, colon cancer, indicating that routine immunohistochemical testing, which is not currently in the guidelines for ampullary carcinomas, is warranted. Programmed cell death‐ligand 1 appears to be closely associated with medullary phenotype regardless of mismatch repair status, and targeted therapies can be considered for such cases.